2020
DOI: 10.1007/978-981-15-6202-0_50
|View full text |Cite
|
Sign up to set email alerts
|

Risk Prediction of Kidney Disease Using Machine Learning Strategies

Abstract: Classification is the most commonly applied machine learning technique that classifies large population of records based on the training set and the feature values. The important task of a classifier is to predict categorical class labels and construct a model for the target class. The classification techniques are widely used in the emerging research fields of bioinformatics. Prediction of disease that is chronic in nature is a big challenge for medical experts. Thus, in the field of bioinformatics, it is vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…Table 13 presents the comparison of performance between the previous studies and our work on the same dataset. In our work, the Relief-F feature selection methods have achieved the best performance for the testing results and cross-validation results using DT and GBT Classifier compared to the other existing works [ 23 , 24 , 26 , 27 , 30 ]. Also, our work is different from the other existing works [ 22 , 25 ] because it registered the results for both the training set and the testing set, and it has achieved the best performance.…”
Section: Experiments and Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…Table 13 presents the comparison of performance between the previous studies and our work on the same dataset. In our work, the Relief-F feature selection methods have achieved the best performance for the testing results and cross-validation results using DT and GBT Classifier compared to the other existing works [ 23 , 24 , 26 , 27 , 30 ]. Also, our work is different from the other existing works [ 22 , 25 ] because it registered the results for both the training set and the testing set, and it has achieved the best performance.…”
Section: Experiments and Resultsmentioning
confidence: 78%
“…The results showed that RF with Random Forest feature selection had achieved the best performance with 98.8% accuracy. In [ 26 ], the genetic search algorithm has been used to select the most important features from the CKD dataset. Decision Table, J48, Multilayer Perceptron (MLP), and NB have been applied to both full features and the selected features.…”
Section: Related Workmentioning
confidence: 99%
“…Jena et al, [12] have categorised recent advancements in imaging technology, including terahertz (THz) pulse imaging and dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI). from a summary of biological image analysis.…”
Section: Literature Surveymentioning
confidence: 99%
“…The key features from the CKD dataset were chosen using the genetic search algorithm in [17]. Both the whole set of features and the chosen features have been subjected to DT [18], the authors employed three base-learners KNN, DT and NB along with two ensemble techniques, Bagging and Random Subspace methods-to predict CKD.…”
Section: Svm and Ann Correlation Coefficientsmentioning
confidence: 99%